2015
DOI: 10.3329/updcj.v5i1.25822
|View full text |Cite
|
Sign up to set email alerts
|

Muskuloskeletal disorders among dental surgeons at selected private dental hospitals in Dhaka city

Abstract: A descriptive cross-sectional study was conducted among 96 dental surgeons at selected private dental hospitals in Dhaka city (North). The objective of the study was to find out musculoskeletal disorders within dental surgeons at selected private dental hospitals in Dhaka city during the period between September to November 2012.Convenient sampling technique was used and information was gathered by face to face interview with a pre tested semi structured questionnaires. Among the respondents, 43.8% were of in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
1
Order By: Relevance
“…Regarding job related characteristics it was found that the mean professional experience, the mean practicing hours per week were 12.6 (±5.1) years, with range 6 -32 years, 46.5 (±13.5) hours, with range 21-96 hours respectively and average number of patients attended per day was 10 (±4.9) with range 3 -30 patients, which was close to the study findings by Batham et al [8] The current study result shows that 63.9%, 47.3% of the participants reported pain and discomfort in at least one body region in the last 12 months and the last 7 days respectively, quite higher prevalence observed in at least one body region in the past 12 months in different studies like 79% (n=2166) in Gupta et al [9] , 83.1% (n=213) in Saxena et al [10] , 86.8% in KiHun et al [11] , 92% in Batham et al [8] . In comparison to present study much higher prevalence of MSDs among the dental practitioners in past 12 months observed in different countries study like America (76.0%) [12] , India (78.0%) [13] , Australia (87.2%) [14] , Poland (92.0% ) [15] , Brazil (65.6%) [16] , Saudi Arabia (77.9%) [17] and in Bangladesh a study by Jahan et al [18] found that 90.0% dental practitioners were suffering from musculoskeletal pain during work in last 3 months. The overall prevalence of MSDs in dentistry differs from 63 -93 % worldwide.…”
Section: Discussioncontrasting
confidence: 67%
“…Regarding job related characteristics it was found that the mean professional experience, the mean practicing hours per week were 12.6 (±5.1) years, with range 6 -32 years, 46.5 (±13.5) hours, with range 21-96 hours respectively and average number of patients attended per day was 10 (±4.9) with range 3 -30 patients, which was close to the study findings by Batham et al [8] The current study result shows that 63.9%, 47.3% of the participants reported pain and discomfort in at least one body region in the last 12 months and the last 7 days respectively, quite higher prevalence observed in at least one body region in the past 12 months in different studies like 79% (n=2166) in Gupta et al [9] , 83.1% (n=213) in Saxena et al [10] , 86.8% in KiHun et al [11] , 92% in Batham et al [8] . In comparison to present study much higher prevalence of MSDs among the dental practitioners in past 12 months observed in different countries study like America (76.0%) [12] , India (78.0%) [13] , Australia (87.2%) [14] , Poland (92.0% ) [15] , Brazil (65.6%) [16] , Saudi Arabia (77.9%) [17] and in Bangladesh a study by Jahan et al [18] found that 90.0% dental practitioners were suffering from musculoskeletal pain during work in last 3 months. The overall prevalence of MSDs in dentistry differs from 63 -93 % worldwide.…”
Section: Discussioncontrasting
confidence: 67%